Articulatory parameters in consonant production after tumour surgery: a real-time MRI investigation - MÁDY, Katalin; BEER, Ambros (Archives of Acoustics, 2007)
This study introduces a technique used in clinical research of speech production for the first time: real-time magnetic resonance imaging (MRI). Our goal was to show the clinical relevance of the use of real-time MRI in speech production. Based on the MRI recordings, four parameters of consonant production were tested: (1) localisation of minimal distance, (2) length of constriction, (3) minimum distance and (4) difference of minimum and maximum distance in front of the uvular region. In the preoperative analysis, parameters (1), (2), and (3) are ranked for the sounds /l/, /s/, /S/, and /x/ from minimum to maximum and parameter (4) inversely. The postoperative results show that this hierarchy is only maintained for parameter (3): minimum distance. The postoperative outcome regarding the other parameters becomes unsystematic depending on the severity of the impairment.